Southwest Research-Extension Center, Field Day 1999 (Kansas Agricultural Experiment Station Research Reports, 1999)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1999; SRP837; crops; tillage; irrigation; insect control; weed science